Education and diversity: The territorialization of education in LDB modalities (Revista Contexto & Educação, 2025)
This article presents it explores the contributions of the teaching modalities provided for by the National Education Guidelines and Bases Law (LDB) to guarantee the right to education within the territorialities of specific social groups, such as peasants, indigenous people, quilombolas and, more recently, gypsies . It highlights the relevance of studying the regulations that regulate these modalities, approaching them as fundamental human rights as established in Law No. 9,394/1996 and in other resolutions and opinions. The research is based on a documentary methodology, resulting in a review article. Land and territory are considered central elements in the fight against educational inequality, and the article recognizes diversity as a crucial factor in the search for overcoming social inequalities through the construction and implementation of public educational policies. The analysis seeks to contribute to the debate and research on the role of schooling in human formation, highlighting the importance of an approach that respects and integrates the cultural and territorial specificities of these groups. The study is expected to offer valuable insights for the formulation of more inclusive and equitable educational policies and practices.
Keywords: Diversity; Teaching Modalities; Legislation; Territoriality